Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Spiritual terhadap Kinerja Karyawan pada CV Polaris Surabaya - Dita Nanda Pratiwi; Handy Aribowo (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of intellectual intelligence, emotional intelligence, and spiritual intelligence on the performance of employees at CV Polaris Surabaya. The background of this research is based on the strategic role of human resources as the company's main asset, acting as planners, implementers, and controllers in achieving organizational goals. This study employs a quantitative approach with a correlational design, collecting data through questionnaires and observations. The population of this study comprises all employees of CV Polaris Surabaya, with a sample of 100 respondents selected using a saturated sampling technique. Data analysis was conducted to examine the influence of each variable both partially and simultaneously on employee performance. The results indicate that intellectual intelligence, emotional intelligence, and spiritual intelligence individually have a positive and significant effect on employee performance. Furthermore, these three variables simultaneously contribute significantly to improving employee performance at CV Polaris Surabaya. Based on these findings, it can be concluded that intellectual, emotional, and spiritual intelligence are crucial factors in enhancing employee performance, suggesting that the company should pay more attention to developing these aspects of intelligence to achieve better organizational goals.”